Structural substitutions on the methoxybenzene ring retain the biological activity of the zaxinone mimics MiZax3 - Wang, Jian You; Jamil, Muhammad; Tareq Berqdar, Lamis M.; Takahashi, Ikuo; Ota, Tsuyoshi; Asami, Tadao; Al-Babili, Salim (Frontiers in Plant Science, 2025)
The plant growth regulator zaxinone is essential for proper rice growth and development. Additionally, zaxinone and its two synthetic mimics, MiZax3 and MiZax5, have been shown to significantly promote crop growth and reduce infestation by the root parasitic plant Striga by suppressing strigolactone (SL) production, highlighting their potential for field application. Here, we developed 4 new MiZax through structural modifications of the methoxybenzene ring in MiZax3 and evaluated their effects on plant growth and SL exudation. These newly developed mimics enhanced rice growth and reduced SL release without compromising the bioactivity of the lead compound MiZax3. Our findings underscore their potential to guide future chemical design efforts aimed at exploring zaxinone biology.